Overcoming global challenges in stroke prophylaxis in atrial fibrillation: the role of non-vitamin K antagonist oral anticoagulants: - Massaro, Ayrton; Giugliano, Robert P.; Norrving, Bo; Oto, Ali; Veltkamp, Roland (International journal of stroke, 2016)
Atrial fibrillation is the world's most common sustained cardiac arrhythmia and is associated with a significantly increased risk of stroke. The global burden o...
Gesehen am 12.05.2020